Efficacy and acceptability of adjunctive psychological and pharmacological interventions for treatment-resistant depression: protocol for a systematic review and network meta-analysis. Issue 5 (14th May 2019) - Husain, Muhammad Ishrat; Strawbridge, Rebecca; Carter, Ben; Jones, Brett D M; Young, Allan; Carvalho, Andre F
Abstract : Introduction: Major depressive disorder (MDD) is a common debilitating illness worldwide. The vast majority of patients with MDD will not achieve remission with first-line treatment and despite the availability of different treatment modalities, at least one-third of patients experience treatment-resistant depression (TRD). There continues to be a paucity of research focused on treatment options for patients with TRD thus treatment decisions are largely based on patient and clinician preference as opposed to evidence-based practice. Herein we propose a systematic review and network meta-analysis (NMA) of available pharmacological and psychological augmentation treatments for TRD, to inform evidence-based management of TRD. Methods and analysis: We plan to conduct a search of electronic databases (MEDLINE and ISIWEB) of all dates from inception for randomised controlled trials of pharmacological and psychological augmentation interventions for adults with TRD. Articles for review will be included based upon consensus from two authors. Pharmaceutical companies will be contacted for access to any unpublished data. An NMA will compare the effectiveness pharmacological adjunctive agents for TRD using preanalysis/postanalysis, assuming consistency and transitivity. Ethics and dissemination: This project does not require research ethics board approval. The dissemination plan is to present findings at international scientific meetings and publishing results in a peer-reviewed academic journal. PROSPERO registration number: CRD42019132588.